Challenging Behaviors in Young Children: The Role of Parenting Consistency in a Multigenerational Family - Maria Angela Andriono; Agnes Maria Sumargi (ANIMA Indonesian Psychological Journal, 2019)
This study aimed to examine differences in challenging behaviors between young children in multigenerational families whose caregivers had consistent and those with inconsistent parenting. Participants were 73 pairs of mothers and grandparents who had children between the age of 2-6 years old in Surabaya and Sidoarjo. Purposive sampling was used to select participants and two scales included were the PSDQ (Parenting Styles and Dimensions Questionnaire) and CAPES (Child Adjustment and Parent Efficacy Scales). A one-way ANOVA was performed to compare children’s challenging behaviors between caregiver groups with consistent-effective parenting, consistent-ineffective parenting, consistent-somewhat effective parenting, inconsistent-ineffective parenting, and inconsistent-somewhat effective parenting. Results showed that there was a significant difference of children’s challenging behaviors at the p < .05 level for the five groups [F(4.68) = 5.73; p = .00] . Compared to other parenting styles, caregivers with consistent-effective parenting had children with the lowest level of challenging behaviors.